Sustainable development and the EPA negotiations (2007)
Opines that lessons learnt over the last 30 years should be used to create international trade agreements that not only seek to integrate developing countries into the global economy, but are in and of themselves pro-development instruments. Notes that these agreements should not focus solely on trade liberalisation policies and the negotiation of trade rules for market access in favour of developing countries' exports. Sees these aspects of international trade agreements as being important but insufficient if development and equity are the goals.
Keywords: SUSTAINABLE DEVELOPMENT